Comparative Analysis of Employees Commitment in Old and New Generation Banks in Ilorin Metropolis - Mawoli, Mohammed Abubakar; Olanrewaju, Bolawa Toun (NIU Journal of Social Sciences, 2021)
This study examines whether the level of employees’ commitment in the Old Generation Banks is significantly different from what obtains in the New Generation Banks in Ilorin metropolis, among others. Employees of Deposit Money Banks operating in Ilorin metropolis constitute the population of the study, out of which 410 and 535 employees are from Old and New Generation Banks respectively. Simple random sampling technique was applied in selecting 146 and 191 staff of the Old and New Generation Banks respectively and subsequently surveyed using a close-ended questionnaire instrument. The study employed percentages, mean and standard deviation descriptive statistical tools to summarize the research data for further statistical processing. Also, the study employed Mann-Whitney U-Test inferential statistical tool to test the research hypotheses. The study found that there is no significant difference in the employees’ organizational commitment of the Old and New Generation Banks. The study, therefore, recommends that either of the banks should focus on improving employees’ level of commitment as a differentiation strategy for gaining competitive human resources advantage necessary for employee retention, talent attraction, favorable customer switching, and business growth and performance. Keywords : Deposit money banks, competition, employees, organizational commitment, employee retention